The Phenomenon of Winning Against an Empty Box in the Simultaneous Regional Head Elections of 2024 - Felix Avian Reandrianta; Edi Pranoto (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The phenomenon of the empty box winning in the 2024 Simultaneous Regional Head Election (Pilkada) reflects public dissatisfaction with the existing political process, particularly concerning the dominance of single candidates. The presence of the empty box as an alternative option highlights structural problems within Indonesia's democratic system, which limits political participation and reduces public representation. Although regulated in the Regional Election Law, this phenomenon reveals a lack of trust in the nomination mechanism, which is neither inclusive nor transparent. This study analyzes how the empty box phenomenon serves as a protest symbol against the lack of diversity in election choices and its impact on political participation. The author argues that to improve the quality of Indonesia's democracy, reform in the nomination system and political participation is necessary to create a more representative and accountable government. This reform must also be accompanied by better political education for the public.